Gambaran Perilaku Kemandirian Anak Usia Pra Sekolah pada Ibu Yang Bekerja dan Tidak Bekerja - Iin Patimah (Jurnal Medika Cendikia, 2016)
This research is motivated to the fact that the field is still a lot of pre-school age children have a low autonomy, children of mothers who work more autonomy than children of mothers who did not work. The purpose of this study is to describe the behavior of the autonomy of pre-school age children (4-6 years) in women who are working and not working. This type of research is quantitative descriptive with a sample of 130 mothers (81 mothers and 49 working mothers do not work) taken with a sampling technique cluster random sampling. Data collection techniques in this study using a questionnaire the child's autonomy. Through the analysis of median concluded both children of working mothers and mothers do not work have a high self-reliance behavior. From the results of these studies suggest that for autonomy that has maintained high with the way the child needs to be taught and conditioned to perform self-care, can fill their own time, children need to be trained to make their own decisions, given a choice so that children get used independently. Continue monitoring of health workers, parents and school instasi also necessary to remember that autonomy is an attitude of individuals who acquired cumulatively during development.